Google vas gleda - Podjed, Dan (Etnolog. Nova vrsta (Ljubljana), 2011)
In the 18th century, the philosopher Jeremy Bentham designed a special building (panopticon), in which people living in cells could be constantly observed from a central "inspection house". The author suggests that a similar but much more extensive observation platform has been created by the development of the World Wide Web. The YouTube portal enables anyone to publish videos of private events and make them publicly available. In a mixture of exhibitionism and voyeurism, amateur pornographic videos, often made without the "actors" being aware, also find their way to internet portals. Another powerful instrument of mutual monitoring is the Google web search engine, which makes it possible to "stalk" people and monitor their habits. In addition, the search engine automatically records search terms, which ultimately reveal what an individual - as well as society as a whole - does and thinks.
Keywords: internet; World Wide Web; svetovni splet; voyeurism; panoptik; exhibitionism; voajerstvo; ekshibicionizem; panopticon